Mary McGrory papers - McGrory, Mary, 1918-2004.; Toll, Tina.
Correspondence, speeches and writings, notebooks and notes, subject files, newspaper clippings, scrapbooks, printed matter, and other papers relating primarily to McGrory's career as a journalist. Documents her work as a book reviewer for the Boston Herald Traveler and columnist for the Washington Post and Washington Star. Subjects include local news, U.S. political affairs, foreign policy, and family matters. Topics represented include arms control; Army-McCarthy Controversy; children; Bill Clinton-Monica S. Lewinsky affair; Iran-Contra Affair; the Iraq War; Ireland; John F. Kennedy's assassination; Middle East; Nicaragua; the Persian Gulf; presidential campaigns from 1956 to 2000; the press; St. Ann's Infant and Maternity Home in Hyattsville, Md.; social security; terrorism and the September 11 terrorist attacks, 2001; Clarence Thomas's nomination to the Supreme Court; Vietnam and the Vietnam War; strike at the Washington Star in 1958 and its demise in 1981; and the entry of the U.S. into World War II. Includes material concerning McGrory's Pulitzer Prize in 1975 for her coverage of the Watergate Affair and notebooks of McGrory's personal assistant, Tina Toll. Individuals represented include George Bush, George W. Bush, Edward Moore Kennedy, John F. Kennedy, Richard M. Nixon, Ronald Reagan, Adlai E. Stevenson, and Clarence Thomas.
Correspondents include Samuel R. Berger, Art Buchwald, Blair Clark, Max Cleland, Bill Clinton, Andrew Mark Cuomo, Mario Matthew Cuomo, George Darden, Maureen Dowd, Sam J. Ervin, Gerald R. Ford, Barney Frank, Phil Gailey, Newt Gingrich, Barry M. Goldwater, Donald E. Graham, Anthony Lewis, Gould Lincoln, Sol M. Linowitz, Gordon Manning, Abigail Q. McCarthy, Eugene J. McCarthy, David G. McCullough, Ralph McGill, George S. McGovern, Sarah M. McGrory, Martin T. Meehan, Daniel P. Moynihan, Newbold Noyes, Robert Redford, Elliot L. Richardson, Tim Russert, Peter F. Secchia, Sargent Shriver, Stephen J. Solarz, Thomas Winship, Bob Woodward, and Edwin M. Yoder.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Rare Book and Special Collections Division.
Library of Congress Serial and Government Publications Division.
Library of Congress Prints and Photographs Division.
Library of Congress General Collections.
Journalist. Full name: Mary Dorothy McGrory.
Keywords: Berger, Samuel R. -- Correspondence; Buchwald, Art -- Correspondence; Bush, George, -- 1924-; Bush, George W. -- 1946-; Clark, Blair, -- 1917-2000 -- Correspondence; Cleland, Max, -- 1942- -- Correspondence; Clinton, Bill, -- 1946-; Clinton, Bill, -- 1946- -- Correspondence; Cuomo, Andrew Mark, -- 1957- -- Correspondence; Cuomo, Mario Matthew -- Correspondence; Darden, George, -- 1943- -- Correspondence; Dowd, Maureen -- Correspondence; Ervin, Sam J. -- 1896-1985 -- Correspondence; Ford, Gerald R., -- 1913-2006 -- Correspondence; Frank, Barney, -- 1940- -- Correspondence; Gailey, Phil -- Correspondence; Gingrich, Newt -- Correspondence; Goldwater, Barry M. -- 1909-1998 -- Correspondence; Graham, Donald E., -- 1945- -- Correspondence; Kennedy, Edward M. -- 1932-2009.; Kennedy, John F. -- 1917-1963.; Kennedy, John F. -- 1917-1963 -- Assassination; Lewinsky, Monica S. -- 1973-; Lewis, Anthony, -- 1927-2013 -- Correspondence; Lincoln, Gould, -- 1880-1974 -- Correspondence; Linowitz, Sol M., -- 1913-2005 -- Correspondence; Manning, Gordon, -- 1917-2006 -- Correspondence; McCarthy, Abigail Q. -- Correspondence; McCarthy, Eugene J., -- 1916-2005 -- Correspondence; McCarthy, Joseph, -- 1908-1957.; McCullough, David G. -- Correspondence; McGill, Ralph, -- 1898-1969 -- Correspondence; McGovern, George S. -- 1922-2012 -- Correspondence; McGrory, Sarah M. -- Correspondence; Meehan, Martin T. -- 1956- -- Correspondence; Moynihan, Daniel P. -- 1927-2003 -- Correspondence; Newbold Noyes, -- 1918-1997 -- Correspondence; Nixon, Richard M. -- 1913-1994.; Reagan, Ronald; Redford, Robert -- Correspondence; Richardson, Elliot L., -- 1920-1999 -- Correspondence; Russert, Tim, -- 1950-2008 -- Correspondence; Secchia, Peter F., -- 1937- -- Correspondence; Shriver, Sargent, -- 1915-2011 -- Correspondence; Solarz, Stephen J. -- Correspondence; Stevenson, Adlai E. -- 1900-1965.; Thomas, Clarence, -- 1948-; Winship, Thomas -- Correspondence; Woodward, Bob, -- 1943- -- Correspondence; Yoder, Edwin M. -- 1934- -- Correspondence; McGrory family; United States. -- Supreme Court; St. Ann's Infant and Maternity Home (Hyattsville, Md.); Boston Herald traveler; Washington post; Washington star; American newspapers -- Massachusetts -- Boston; American newspapers -- Washington (D.C.); Arms control; Army-McCarthy Controversy, 1954.